Laser Based Measurement for Liquid Refractive Index - Al-Dahan, Ziad T.; Al-Magazachi, Sinan A.. (Nahrain University College of Engineering Journal, 2011)
One of independent laser-based technique is presented to measure liquid refractive index, which is important in medical and other applications. Semiconductor laser diode of 630nm wavelength serves as alight source for measurement. Results are presented for different types of liquids in two methods, one of these methods is done by matlab language as the theoretical result, the other method is the opti-cad program which represented the simulation results. Good matching found between the two the theoretical and simulation results. The experimental setup is high precision, non-contact between the tools and the liquid which is under test